Minat Siswa Melanjutkan Studi Ke Perguruan Tinggi Ditinjau Dari Tingkat Pendapatan Orang Tua Dan Motivasi Belajar Pada Siswa Kelas XII IPS SMA Negeri 1 Andong Tahun Ajaran 2016/2017 - Damarjati, Wisnu, Drs. Sudarto HS, MM (2017)
The purpose of this study was to determine: 1) the effect of the income level of parents against the interest of the students to continue their studies to university, 2) effect of learning motivation against the interest of the students to continue their studies into higher education, 3) the influence between the income level of parents and learning motivation toward interest students continue their studies to university. This research is a quantitative associative. The population in this study were students of class XII IPS SMA Negeri 1 Andong by the number of students 127 students. Samples taken as many as 95 students with proportional random sampling technique. Data taken and documentation obtained through a questionnaire which had previously been trialed and tested for validity and reliability were tested. Data analysis technique used is multiple linear regression analysis, F test, t-test, R2, effective contribution and relative contribution. Based on the analysis of data obtained by multiple linear regression equation as follows: Y = 101.088 + 1.153 X1 + 0.283 X2. The equation shows that interest to continue their studies to university influenced by the level of parental income and motivation to learn. Based on the analysis and discussion can be concluded that: (1) The income level of parents has positive influence on the student's interest to continue their studies to university. This is proven by regression analysis to obtain tcount> ttable namely 3.298> 1.986 with 0.001 significance value <0.05. (2) motivation to learn a positive influence on the student's interest to continue their studies to university. This is proven by regression analysis to obtain tcount> ttable namely 7.067> 1.986 with 0.000 significance value <0.05. (3) the level of parental income and motivation to learn together positive effect on student interest to continue their studies to university. This is proven by regression analysis to obtain the value fcount> Ftable is 30.636> 3.10 with significant value 0.000 <0.05. (4) Variable income level of parents contribute effectively amounted to 7.24%. Learning motivation variables contribute effectively amounted to 32.72%, with a coefficient of determination (R2) of 0,400, or 40.0%, while 60.0% are influenced by other variables not examined.